Подолання «мови ворожнечі» в інклюзивній художній літературі (на матеріалі твору Аудгільд Сульберґ «Хто проти суперкрутих») - Землянська, Аліна Вікторівна; Zemlianska, A.V.; Землянський, Анатолій Миколайович; Zemlianskyi, A.M. (My University, 2022)
UKR: У статті повість А. Аудгільд Сульберґ розглядається в контексті інклюзивної літератури з позицій «мови ворожнечі», яку виказують по відношенню до головної героїні-аутсайдера однолітки. Проаналізовано рівні прояву вербальної дискримінації. ///////// ENG: The article examines A. Audhild Solberg's story in the context of inclusive literature from the standpoint of the «hate speech» expressed towards the protagonist, an outsider in her school. There were analyzed the levels of verbal discrimination.
Overcoming «hate speech» in inclusive fiction (based on the work of A. Audhild Solberg «Who is against the superbitches»)
Keywords: інклюзивна художня література; вербальна дискримінація; мова ворожнечі; людина з особливими потребами; inclusive fiction; hate speech; person with special needs; verbal discrimination